Combined Analysis of EGFR and PTEN Status in Patients With KRAS Wild-Type Metastatic Colorectal Cancer. Issue 40 (October 2015) - Chen, Yu; Shi, Yi; Lin, Jing; Ye, Yun-bin; Wang, Xiao-jie; Chen, Gang; Guo, Zeng-qing
Abstract : Abstract: To determine the relationship between the expression of phosphatase and tensin homologue (PTEN) and epidermal growth factor receptor (EGFR) in metastatic colorectal cancer (mCRC) and the clinical outcome of cetuximab-containing chemotherapy. A total of 158 consecutive mCRC patients with wild-type KRAS status who received chemotherapy with or without cetuximab, and for whom tumor tissue was available, were enrolled. The EGFR and PTEN expression was determined by immunohistochemistry (IHC). A total of 158 mCRC patients with wild-type KRAS status were enrolled in the study; 51 patients received chemotherapy combined with cetuximab, 107 patients received chemotherapy alone. Patients who received chemotherapy combined with cetuximab had longer overall survival (OS) compared with patients who received chemotherapy alone. High EGFR expression was detected in 60 patients (38.0%), while normal PTEN expression was detected in 60 patients (59.5%). The PTEN status was significantly related with the histological grade. For patients who received chemotherapy combined with cetuximab the median OS of patients with high-expression of EGFR was longer than the OS of patients with low EGRF expression; 25.0 versus 19.0 months, P  = 0.002. For patient with normal PTEN the median OS were longer than the median OS for patients with loss of PTEN; 24.0 versus 19.0 months, P  = 0.026. The overall response rate (ORR) had a borderline association with EGFR and PTEN expression ( P  = 0.055 and 0.048, respectively). In a multivariate analysis, ECOG PS, EGFR status, chemotherapy ± cetuximab, and the interaction of EGFR or PTEN and chemotherapy ± cetuximab were independent prognostic factors for OS. Our findings show that chemotherapy combined with cetuximab demonstrated encouraging antitumor activity for mCRC patients with wild-type KRAS status. Especially, those who have high EGFR expression or normal PTEN expression were more likely to benefit from such a treatment strategy. Subsequent studies in clinical trial cohorts will be required to confirm the clinical utility of these markers.